1997
DOI: 10.1099/00207713-47-1-46
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Genus Actinomyces Based on 16S rRNA Gene Sequences: Description of Arcanobacterium phocae sp. nov., Arcanobacterium bernardiae comb. nov., and Arcanobacterium pyogenes comb. nov.

Abstract: A systematic phylogenetic analysis of the genus Actinomyces was performed. The 16S rRNA gene sequences of 13 Actinomyces species, an unnamed Actinomyces strain (ATCC 49338), and an Actinomyces-like isolate from sea mammals were determined. Comparative sequence analysis with closely related taxa revealed phylogenetic diversity and internal structure within the genus Actinomyces. In addition, some members of other genera (viz., the genera Arcanobacterium, Mobiluncus, and Rothia) were shown to be phylogenetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…Colonies are circular, smooth, and slightly convex with a glassy appearance and diameters range from 0.2 to 0.5 mm 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies are circular, smooth, and slightly convex with a glassy appearance and diameters range from 0.2 to 0.5 mm 1.…”
Section: Introductionmentioning
confidence: 99%
“…was proposed 3. It was classified as part of the genus Arcanobacterium 1 and was later reclassified as part of the genus Trueperella 4.…”
Section: Introductionmentioning
confidence: 99%
“…In Bergey's Manual of Systematic Bacteriology (Schaal, 1986), 10 species were included in the genus Actinomyces, with two additional organisms listed as species incertae sedis. Since Bergey's Manual o j Systematic Bacteriology was published, knowledge of the phylogenetic interrelationships of members of the genus Actinomyces has improved considerably (Pascual Ramos et al, 1997). In particular, comparative 16s rRNA gene sequencing has shown that the genus Actinomyces is phylogenetically very heterogeneous.…”
mentioning
confidence: 99%
“…Much less is known about the range of Actinomyces-like organisms in domestic and wild animals. There are, however, indications (Pascual et al, 1997a(Pascual et al, , 1999 veterinary organisms will result in the recognition of much greater Actinomyces diversity, leading to a better understanding of their host distribution and clinical significance. In this article, we report the characteristics of two strains of an unusual Actinomyces species isolated from dogs.…”
mentioning
confidence: 99%
“…The genus Actinomyces as presently defined is not monophyletic and consists of several rRNA lineages worthy of separate generic status (Pascual et al, 1997a(Pascual et al, , 1999. The type species of the genus, Actinomyces bovis, falls into a distinct and robust rRNA cluster which embraces several species (viz : Actinomyces bowdenii, Actinomyces denticolens, Actinomyces howellii, Actinomyces gerencseriae, Actinomyces israelii, Actinomyces naeslundii, Actinomyces slackii, Actinomyces urogenitalis and Actinomyces viscosus) which can be regarded as the genus Actinomyces sensu stricto.…”
mentioning
confidence: 99%